O nascimento da Biopolítica na Província de Mato Grosso (1719- 1840) - Reis, Cristiano Antonio dos (2018)
This thesis defends the idea of the birth of biopolitics in the province of Mato Grosso, conceptually supported by the researches of the philosopher Michel Foucault. In this sense, we sought to demarcate historically the passage from a form of exercise of power based on sovereignty based between premises of good government and reason of state for a form of exercise of power based on liberal thinking. his approach sought to understand how the problem of population became present in the speeches of the presidents of Mato Grosso province in the management of freedom, which ironically produced a series of population control devices.